Proceedings of the Tenth ACM International Conference on Future Energy Systems 2019
DOI: 10.1145/3307772.3328305
|View full text |Cite
|
Sign up to set email alerts
|

Identifying infected energy systems in the wild

Abstract: The 2016 Mirai outbreak established an entirely new mindset in the history of large-scale Internet attacks. A plethora of Mirai-like variants have emerged in the last two years that are capable to infiltrate any type of device. In this paper we provide a 7-month retrospective analysis of Internet-connected energy systems that are infected by Mirai-like malware variants. By utilizing network measurements from several Internet vantage points, we demonstrate that a number of energy systems on a global scale were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
(9 reference statements)
0
7
1
Order By: Relevance
“…6, each scanner may scans a maximum of 15 ports with a minimum of 2 in every scanning session. Hence, in contrast with discussions (e.g., [6], [8]) on the full randomness of scanning strategies, we identify that even new Mirai variants have a carefully crafted and strategic scanning procedure.…”
Section: A Scanning Phasecontrasting
confidence: 60%
See 3 more Smart Citations
“…6, each scanner may scans a maximum of 15 ports with a minimum of 2 in every scanning session. Hence, in contrast with discussions (e.g., [6], [8]) on the full randomness of scanning strategies, we identify that even new Mirai variants have a carefully crafted and strategic scanning procedure.…”
Section: A Scanning Phasecontrasting
confidence: 60%
“…The seminal study in [5] was the first to profile the original 2016 Mirai botnet outbreak and contributed towards the Internet-wide, AS-level analysis as well as the impact of shared source code which led to the proliferation of Mirai variants. Moreover, the work in [3] and [6] assessed the impact of Mirai-like variants on industrial control systems (ICS) and how Mirai-like variants exploit DNS records respectively. Nonetheless, all aforementioned studies didn't capture the modern scanning characteristics of new variants and in parallel did not provide a recent overview of the Mirai-like structural properties (i.e., centralised or P2P) as conducted in this work.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The situation of cyberattacks against ICS has been investigated by monitoring devices, botnets, and globally deployed honeypots [2]. Marnerides et al reported that ICS networks were compromised due to non-ICS devices such as routers, servers, and IoT devices that were used as footholds for lateral movement [37].…”
Section: B Attack Observationmentioning
confidence: 99%